Psychological Side in Literary Works and Its Implication on English Teaching - Dwi Rahayu, Titis (Griya Cendikia, 2022)
Literature is the language (words, language style) used in books but is not an everyday language. On the other hand, psychology itself is a branch of science that studies behavior and mental processes experienced and done by humans. Psychology and literature are two different but related aspects of knowledge. Literary works provide additional material for practice of grammar (grammar), learning vocabulary, and translation. This can provide knowledge about the importance of the implications of literary works in teaching English and show some negative and positive things contained in the implications in schools and teaching literature in English teaching.